Pendampingan Program Parenting Pada Ibu Rumah Tangga di Desa Mariana Kecamatan Banyuasin - Winda Eprilia; Syarifuddin Syarifuddin; Marsela Arneta; Faradita Dwi Indriani; Monica Anggraini; Viki Yuliandari; Pepi Lestari; Ade Lina Suryani; Retno Wahyu Lestari; Lasmiyanti Lasmiyanti; Evie Irawati (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
The background of this research and activity is due to the low understanding of parents about proper parenting in accordance with the growth and development of children. The research aims to implement a parenting program in Mariana Village, Banyuasin District and increase knowledge about parenting for mothers in Mariana Village, Banyuasin District. This research method is descriptive qualitative with field studies that directly apply this parenting program to mothers in Mariana Village, Banyuasin District. The data collection techniques in this study were (1) Post test and Pretest the knowledge of Mariana's mothers about parenting. (2) Field observation. The results of this study are: (1) Increased understanding of mothers in Mariana Village, Banyuasin District regarding parenting that is appropriate for children's growth and development. (2) Formation of parenting skills for mothers in Mariana Village, Banyuasin District Parenting Program Activities; Parenting; Mariana Village Women.